MAKING A TISSUE HOLDER DECORATED WITH SAND - Atthaya Ershandi; Zulfahita Zulfahita (STKIP Singkawang, 2020)
The tissue holder that we made is used to store tissues, so they look more attractive and tidy. This tissue holder is usually used as a complementary decoration on the living room table. The tissue holder that we made is made of thick cardboard or commonly called board paper, which is decorated with sand mixed with brown food coloring and white fox glue, so that the tissue holder doesn't look plain, so it can make the tissue holder more beautiful and attractive. when created with the sand. The tissue holder that we make is also cheap and maybe this item is often heard from among the public. However, rarely do anyone make it decorated with sand, so we will try to make a tissue holder. The materials we use are readily available and cheap. The thing that is needed in making a tissue holder is creative. With creativity, unique and funny shapes will be created. From this tissue holder that we make, it is used for decoration and other uses. Adding added value to these objects so that they have high economic value and can become a business opportunity. By utilizing existing materials or objects, it can create or create a good and unique work that can be of high value and economic value. This tissue holder is useful as decoration and other uses. Apart from being an artistic value.